2019
DOI: 10.1176/appi.ps.201800389
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mental Health Services by Children With Mental Disorders in Two Major Cities in Brazil

Abstract: Objective: To describe lifetime mental health service use in children diagnosed with mental disorders in two major cities in Brazil and to identify characteristics associated with unmet needs. Methods: The High Risk Cohort Study is a community study conducted in two major Brazilian cities. 2,511 6-12 years old children were assessed and 652 were diagnosed with at least one mental disorder. The current study analysed a subsample of 651 children with complete information on mental health service use. Results: 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 13 publications
2
30
1
1
Order By: Relevance
“…46 It should be noted that adequate treatment is not provided to 81% of 6-12 year old Brazilian children with mental disorders. 22 It is noteworthy that the prevalence of delayed socioemotional development in our sample (30.3%) was two to three times higher than that detected in U.S. samples using the ASQ-SE (ranging from 7.5 to 12.5%). 47,48 In our sample, children with MBDD faced higher parental stress, parental psychopathology, and lower social capital.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…46 It should be noted that adequate treatment is not provided to 81% of 6-12 year old Brazilian children with mental disorders. 22 It is noteworthy that the prevalence of delayed socioemotional development in our sample (30.3%) was two to three times higher than that detected in U.S. samples using the ASQ-SE (ranging from 7.5 to 12.5%). 47,48 In our sample, children with MBDD faced higher parental stress, parental psychopathology, and lower social capital.…”
Section: Discussioncontrasting
confidence: 63%
“…Specifically, the Sã o Paulo metropolitan area had an estimated population of 3,178,893 children and adolescents, with 400,000 exhibiting mental health problems. 20 Despite the recognition of psychiatric disorders as a major cause of impairment in children and adolescents, with lasting effects and burden for caregivers, mental health is still neglected 21,22 Likewise, the notion that early identification of risk factors is critical to prevent the development and persistence of disorders over time 23 has not been sufficient to bridge the huge gap between mental health needs and the resources available, especially in LMICs. 24 Preventive interventions, including social skill training for children, child-rearing practices for parents, and support for teachers concerning at-risk children, have shown some efficacy in reducing the persistence or incidence of later mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The High-Risk Cohort Study for the Development of Childhood Psychiatric Disorders (HRC), an ongoing longitudinal cohort study conducted in Brazil, is highlighted here due to its innovative methodology among LMICs that includes psychopathology, cognitive assessments, genetics, and neuroimaging. Our search elicited 12 studies resulting from the HRC, including the following topics and methodologies: functional connectivity and depression, 11 the role of inflammation in mental health problems in children, 12 cortical structure in children and adolescents with psychiatric disorders, 13 spontaneous brain activity involved in obsessive compulsive symptoms, 14 self-harm, 15 perinatal complications and mental health problems in children and adolescents, 16 dynamic functional connectivity and psychopathology, 17 attention bias to threat, 18 the association between obsessive compulsive symptoms and psychopathology/behavior problems, 19 the genetics of attention-deficit/hyperactivity disorder (ADHD), 20 the utilization of mental health services by children, 21 and the economic impact of childhood mental disorders. 22 …”
Section: Resultsmentioning
confidence: 99%
“…However, there is a lack of studies that evaluate the effectiveness of implementation of these policies for issues such as prevention, promotion, diagnosis, and treatment (Tomaz et al, 2016). Supervision of child health and neurodevelopmental indicators in Brazil is part of pediatric childcare actions; however, Brazilian studies showed the urgent need to implement programs to help reduce unmet mental health needs, inequalities, and increase planning strategies to reduce barriers for mental care in the childhood (Paula et al, 2014;Fatori et al, 2019).…”
Section: Introductionmentioning
confidence: 99%